Chlorine Adsorption of Activated Carbons, Carbon Molecular Sieves and Carbon Nanotubes - Xue, Jian-Wei; Wen, Xiao-Guang; Zhao, Hui-Ling; Lv, Zhi-Ping; Li, Fu-Xiang (Asian Journal of Chemistry, 2012)
Activated carbon, carbon molecular sieves and carbon nanotubes as ordered porous carbon materials, which have huge surface areas and special developed holes are investigated and compared by their chlorine adsorption properties in this paper. The adsorption properties of chlorine are investigated by pressure composition temperature instrument and characterized by X-ray diffractometer, Fourier transform infrared spectroscopy and scanning electron microscopy. The data is obtained at a temperature range of 273 K-323 K and pressure is in the range of 0-0.35 MPa. Among the three porous carbon materials, carbon nanotubes is most efficient in adsorption of chlorine and the adsorption capacity can reach 37.51 % at temperature 30 ºC and under the pressure 0.332 MPa. The experimental data shows that the chlorine adsorption capacity influenced by temperature and pressure. Pore volume and aperture type are main factors attribute to the capacity difference. Activated carbon, carbon molecular sieves and carbon nanotubes are found to be potential candidates for adsorbing chlorine.